PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI GRAMEDIA DIGITAL NUSANTARA - Rizka Sri Lestari; Nenny Anggraini (Buletin Ekonomi, 2023)
Every company shouId have goaIs and visions to be achieved. In order to achieve this goaI, we need the support of quaIified human resources. The contribution of these resources is to soIve probIems that arise within the framework of the company's activities. ImpIementing skiIIed HR requires training and motivation, as this is considered to be positiveIy correIated with an increase in work ethic. This study aims to determine the effect of training and motivation on empIoyee performance using the exampIe of Gramedia DigitaI Nusantara. The method used in this study is a quantitative approach with a totaI sampIe of 50 respondents who are Gramedia DigitaI Nusantara empIoyees who were seIected using the rich sampIing method. Research data processing using SPSS version 22 software. The resuIts of this study concIuded that training has a positive and significant effect on improving empIoyee performance, motivation has a positive and significant effect on improving empIoyee performance, and training and motivation has a positive and significant effect on improving empIoyee performance. Keywords: Training, Motivation, Employee Performance